2007
DOI: 10.1577/m06-016.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Fish Mesohabitat to Flow in a Sand‐Bed Southwestern River

Abstract: We quantified the availability and utilization of habitat types by eight small-bodied cyprinid fish species, including the federally threatened Pecos bluntnose shiner Notropis simus pecosensis, in the Pecos River, New Mexico. The Pecos River is a medium-sized, sand-bed river with a highly variable hydrograph and some reaches characterized by historic and recent periods of flow intermittency. Fish habitat was described in four reaches at flows of 0.05-2.29 m 3 /s by means of a simultaneous, coordinated program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“… References: 1 Dudley and Platania (); 2 Welker and Scarnecchia (); 3 Pollard (); 4 Harrel, Davis and Dorris (); 5 Kilgore Jr. and Rising (1965); 6 Bonner, Wilde, Jimenez and Patiño (); 7 Kehmeier et al. (); 8 Heard et al. (); 9 Gido et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… References: 1 Dudley and Platania (); 2 Welker and Scarnecchia (); 3 Pollard (); 4 Harrel, Davis and Dorris (); 5 Kilgore Jr. and Rising (1965); 6 Bonner, Wilde, Jimenez and Patiño (); 7 Kehmeier et al. (); 8 Heard et al. (); 9 Gido et al.…”
Section: Resultsmentioning
confidence: 99%
“…Western silvery minnow, plains minnow and Red River shiner were reported from backwaters, side channels, mainstream borders and depressional environments (Hesse, ; Houston, ; Kilgore & Rising, ; Welker & Scarnecchia, ). Conversely, sturgeon chub and Pecos bluntnose shiner were reported in swift velocity mainstem habitats (Kehmeier, Valdez, Medley & Myers, ; Ridenour, Starostka, Doyle & Hill, ; Welker & Scarnecchia, ). Despite the commonalities in mesohabitat, habitat partitioning between western silvery minnow and plains minnow has been observed at finer spatial scales.…”
Section: Resultsmentioning
confidence: 99%
“…For example, based on the univariate and bivariate habitat characteristics, Matthews and Hill (1980) and Polivka (1999) found evidence of nonrandom selection of microhabitats by the dominant cyprinid species in the South Canadian River, Oklahoma, but observed little consistency in the types of habitats used by these species. In contrast, Kehmeier et al (2007) reported that small-bodied cyprinids were nonrandom in their use of various habitat types in the Pecos River, New Mexico, but that there was substantial overlap among these habitats in physical and chemical characteristics. It remains unclear if fishes that inhabit the Great Plains streams and rivers have specific habitat requirements or preferences that, as yet, have not been definitively identified or if the inconsistent evidence for specific habitat associations reflects a generalist strategy among these species for coping with life in extremely variable environments.…”
Section: Introductionmentioning
confidence: 92%
“…Although a few deeper pools were encountered outside the sample reaches, the majority of the river could be easily waded and seined. Most of the sampled sites contained five to six mesohabitat types (Kehmeier et al 2007), run and flat mesohabitat types being dominant throughout. Braided reaches contained higher habitat diversity than incised reaches; backwater and slackwater areas occurred along the shore and sandbar margins.…”
Section: Sampling Environmentmentioning
confidence: 99%
“…We evaluated the effectiveness of the removal by estimating numbers of small-bodied fishes at seven sites of the Pecos River between Sumner Dam and Brantley Reservoir ( Figure 1) during September 20-23, 2005. To provide a robust test of the removal method, we selected sites in areas with a representative suite of habitat features (e.g., backwater, flat, parallel plunge, perpendicular plunge, pool, riffle, run, and slackwater; Kehmeier et al 2007). Specific site length was determined by locations where block nets could be effectively set.…”
Section: Pilot Study For the Removal Estimatormentioning
confidence: 99%